CEO compensation and components of earnings in bank holding companies - Clinch, Greg; Magliolo, Joseph (Journal of Accounting and Economics, 1993)
This study analyses the relation between cash compensation of bank CEOs and accounting earnings from selected discretionary transactions. Results indicate that income from discreationary transactions accompanied by cash flow effects is reflected in the CEO compensation function. There is no reliable indication that income from discreationary transactions unaccompanied by cash flows affects compensation. The impact of discreationary earnings on the compensation function varies as a function of firms' ‘nonperforming loans’. We interpret nonperforming loans as a proxy for the firm's future capital position. There is no support for a tax-based explanation for the link between compensation and discreationary earnings.